Tindak Pidana Peredaran Narkotika yang Dilakukan Oleh Anak - Fitri Ida Laela; Suandi Suandi (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2024)
Factors causing children to become perpetrators of criminal acts include the attitude of parents who often commit violence against children. Another cause is the increasing number of perpetrators of crimes committed by children in the family, school and community environment. These value systems conflict with each other with the mindset of children who are growing up. Poverty in the social environment is also a cause of children committing crimes. One example is children and adolescents in the Johar Baru area, Central Jakarta who are often suspects in inter-village brawls. Legal Accountability for Children Who Are Drug Dealers Based on Law Number 11 of 2012 in imposing prison sentences on children as perpetrators of narcotics crimes based on various considerations consisting of aggravating and mitigating considerations shows that judges are only oriented towards prohibited acts which means only oriented towards aggravating considerations.